2012
DOI: 10.1016/j.applanim.2011.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of pair housing are consistent across a diverse population of rhesus macaques

Abstract: Introducing singly housed rhesus macaques (Macaca mulatta) into isosexual pairs is widely considered to improve welfare. The population of laboratory rhesus macaques is heterogeneous on a variety of factors and there is little literature available to directly evaluate the influence of many of these factors on the benefits of pair housing. Subjects were 46 adult female and 18 adult male rhesus macaques housed at the Tulane National Primate Research Center and the Yerkes National Primate Research Center. Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 29 publications
(43 reference statements)
2
68
0
Order By: Relevance
“…These results were not surprising; several studies have found that single housed macaques are more likely to display anxiety and abnormal behaviors, including MSB, compared pair housed animals (Baker et al, 2012a; Baker et al, 2013; Gottlieb et al, 2013a; Schapiro et al, 1996). What was somewhat surprising was the finding that animals housed in protected contact showed the same amount of MSB as single housed monkeys.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…These results were not surprising; several studies have found that single housed macaques are more likely to display anxiety and abnormal behaviors, including MSB, compared pair housed animals (Baker et al, 2012a; Baker et al, 2013; Gottlieb et al, 2013a; Schapiro et al, 1996). What was somewhat surprising was the finding that animals housed in protected contact showed the same amount of MSB as single housed monkeys.…”
Section: Discussionmentioning
confidence: 78%
“…Compared to single housing, full contact pairing, in which two animals live in two adjoined cages, has reliably been shown to correlate with decreased expression of MSB in rhesus monkeys (Baker et al, 2012a; Baker et al, 2013; Gottlieb et al, 2013a; Lutz et al, 2003). In contrast, protected contact, a kind of housing in which two NHPs are separated by a partially open divider that allows some tactile contact, has not always shown the same reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some patterns of alopecia have been reported to match cage mesh patterns and may be due to the friction caused by leaning against the cage sides [30]. This may be more likely to occur in singly housed and older animals, because they tend to be less active than their socially housed or younger counterparts [2,34]. Therefore, although hair-pulling, activity, and cage friction were not directly assessed in the present study, they may have been contributors to hair loss, especially in older animals.…”
Section: Age and Single Housing Effectmentioning
confidence: 99%
“…Among laboratory rhesus macaques ( Macaca mulatta ), about half are housed socially, generally in isosexual pairs; this figure that has changed little in the past decades according to available literature [Baker et al, 2007; Reinhardt, 1994]. It is well established that socially housed rhesus macaques demonstrate well-being that is superior to that of their singly housed counterparts; pair-housed rhesus macaques display more affiliative interactions, physical activity, play, and exploration than singly housed individuals [Baker et al, 2012a; Eaton et al, 1994; Schapiro et al, 1996] and less abnormal, stereotyped, and self-injurious behavior [Baker et al, 2012a; Lutz et al, 2003; Novak, 2003; Schapiro et al, 1996]. Improved welfare as a result of social housing has been demonstrated in both female–female and male–male adult pairs [Baker et al, 2012a; Doyle et al, 2008; Eaton et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that socially housed rhesus macaques demonstrate well-being that is superior to that of their singly housed counterparts; pair-housed rhesus macaques display more affiliative interactions, physical activity, play, and exploration than singly housed individuals [Baker et al, 2012a; Eaton et al, 1994; Schapiro et al, 1996] and less abnormal, stereotyped, and self-injurious behavior [Baker et al, 2012a; Lutz et al, 2003; Novak, 2003; Schapiro et al, 1996]. Improved welfare as a result of social housing has been demonstrated in both female–female and male–male adult pairs [Baker et al, 2012a; Doyle et al, 2008; Eaton et al, 1994]. Pair and group housing may buffer stress for rhesus macaques as they are exposed to research events [Gilbert & Baker, 2011], removed from social groups [Gust et al, 1994], or transported to different facilities [Fernström et al, 2008].…”
Section: Introductionmentioning
confidence: 99%